Analisis Kualitas Kinerja Perawat Ditinjau Dari Beban Kerja dan Motivasi Di Puskesmas Kabupaten Malang - Moch - Masrukin (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Puskesmas is an institution that provides health services at the first level that has direct involvement with the community. The quality of services provided is strongly influenced by health workers, including nurses. There are several factors that need to be considered to improve nurse performance, namely motivation and workload. The purpose of this study was to determine the effect of workload and motivation on the performance quality of nurses at Sumberpucung Health Center and Kepanjen Health Center.Methods: The sample in this study were nurses at the Sumberpucung Health Center and Kepanjen Health Center, namely 100 samples. The data analysis used is multiple linear regression test.Results: There is a significant influence between workload and motivation on the performance quality of nurses at the Sumberpucung Health Center and Kepanjen Health Center, Malang Regency.Conclusion: The conclusion of this study is that there is a significant relationship between motivation and workload on the performance quality of nurses at the Malang District Health Center.